Emotional intelligence as a protective factor against mental health problems of health workers - Mimoza Shahini; Naim Telaku; Idriz Sopjani; Mimoza Kamberi; Dardana Fetahu; Donjeta Murtezaj (Population Medicine)
Introduction Emotional intelligence is regarded as a protective factor among many different groups in the face of adversities, among these has been the COVID-19 pandemic. This study, conducted in 2021 in Kosovo, aims to explore the protective role of emotional intelligence against mental health problems, at the workplace among health and nonhealth workers, and those not working at all.